Detection of condensin I and II in maturing pig oocytes - Lisková, Lucie; Susor, Andrej; Pivonková, Katerina; Sasková, Adéla; Karabínová, Pavla; Kubelka, Michal (Reproduction, fertility, and development, 2010)
The multiprotein complexes known as condensins (I and II) are major players in chromosome dynamics in mitotic and meiotic cells. Here, we report for the first time the detection of different condensin subunits from both complexes in mammalian oocytes. Using immunoblotting analysis we examined expression levels of condensin subunits during meiotic maturation of porcine oocytes. The expression of the core subunit structural maintenance of chromosomes 2 (SMC2), identical in both condensin complexes, did not change significantly during maturation. Similarly, there was no significant change in the expression of the chromosome associated protein (CAP)-H and CAP-H2 subunits, components of condensin I and II, respectively. Conversely, the expression profiles of CAP-G, CAP-D2 (condensin I) and CAP-D3 (condensin II) were more interesting. At least two isoforms of the CAP-D2 subunit were detected, along with three isoforms of the CAP-D3 and CAP-G subunits. We suggest that this diverse migration of subunit isoforms is due to post-translational modification. Earlier, it was reported that non-SMC proteins are phosphorylated by cyclin-dependent kinase 1. In the present study, we analysed the phosphorylation status of the three subunits in oocyte extracts using alkaline phosphatase treatment and we found that at least the fastest migrating form of CAP-D3 was likely to be phosphorylated in maturing porcine oocytes. In addition, the localisation of CAP-H and CAP-H2 subunits was examined using immunofluorescence staining with specific antibodies, as well as following microinjection of their enhanced green fluorescent protein-tagged mRNA into germinal vesicle-stage oocytes. CAP-H was found in the cytoplasm, whereas CAP-H2 was localised within the nucleus.
Keywords: chromozomy; oocyty; Microscopy, Fluorescence; DNA vazebné proteiny; Protein Processing, Post-Translational; Microscopy, Confocal; prasata; Immunoblotting; podjednotky proteinů; Animals; multiproteinové komplexy; Meiosis; Protein Subunits; DNA-Binding Proteins; zvířata; fluorescenční mikroskopie; konfokální mikroskopie; adenosintrifosfatasy; meióza; Multiprotein Complexes; Adenosine Triphosphatases; Chromatin; Swine; ženské pohlaví; imunoblotting; Female; Chromosomes; chromatin; Oocytes; posttranslační úpravy proteinů